2011
DOI: 10.5582/ddt.2011.v5.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Availability of serum corticosterone level for quantitative evaluation of morphine withdrawal in mice

Abstract: Physical dependence on morphine is evidenced by the withdrawal syndromes, including body weight loss, which are induced by the discontinuation of morphine exposure or by the treatment with naloxone, an opioid receptor antagonist. The present study was designed to examine whether the elevation of serum corticosterone (SCS) level induced by naloxoneprecipitated morphine withdrawal was a useful index to quantify the physical dependence on morphine in mice, which was compared with body weight loss induced by nalox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…This is supported by the similar CORT levels of our data and of normal control groups of other studies (Gomez et al, 2000; Nunez et al, 2009). According to the previous studies (Nunez et al, 2009; Ueno et al, 2011), there is evidence of CORT levels rising in rats withdrawn from morphine. However, those studies used passive administration of a high dose of morphine, followed by opioid antagonist-precipitated withdrawal, which can be stressful to animals.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is supported by the similar CORT levels of our data and of normal control groups of other studies (Gomez et al, 2000; Nunez et al, 2009). According to the previous studies (Nunez et al, 2009; Ueno et al, 2011), there is evidence of CORT levels rising in rats withdrawn from morphine. However, those studies used passive administration of a high dose of morphine, followed by opioid antagonist-precipitated withdrawal, which can be stressful to animals.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, we investigated corticosterone (CORT) levels in blood, which is a well-known marker for stress responses. In previous studies, it has been demonstrated that morphine-withdrawn rats show elevated blood CORT levels, which may be caused by stress (Nunez et al, 2009; Ueno et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The withdrawal signs of NIC closely resemble the commonly observed withdrawal signs of opioids (44). It has been reported that an increase in CORT levels is one of the signs of morphine withdrawal and that the magnitude of the increase is an effective, objective, and quantitative indicator of spontaneous and opioid-receptor antagonist-precipitated morphine withdrawal in rodents (45,46). The CORT increase elicited by morphine withdrawal is caused by the activation of A2 adrenergic cells in the nucleus of the solitary tract (47), which is mechanistically similar to the NIC-induced activation of the HPA axis (35).…”
Section: Physical Dependencementioning
confidence: 99%
“…Furthermore, the degree of NLX-induced SCS increase was significantly correlated with the intensity of NLXinduced body weight loss in morphine-dependent mice (27). In these studies, we used large doses of morphine to induce the physical morphine dependence (50, 100, and 200 mg/kg, twice a day for 2 days; a total of 6 days of treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, signs of opioid withdrawal might be useful to evaluate NLX-precipitated NIC withdrawal. In addition, we reported that the degree of SCS elevation is an effective, objective, and quantitative indicator of spontaneous-and NLX-precipitated morphine withdrawal in rodents and that increased SCS levels due to withdrawal reflects the magnitude of morphine withdrawal (26,27). Thus, we used the SCS increase as an objective and quantitative indicator of NLX-precipitated NIC withdrawal.…”
Section: Discussionmentioning
confidence: 99%